PsycEXTRA Dataset 2013
DOI: 10.1037/e616162013-001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music Preference on Complex Task Performance

Abstract: This study examined the relationship between music preference and extraversion on complex task performance in a sample of 34 college students from a small, Christian, liberal arts university. Separated into two groups of high and low extraversion, these 34 participants were invited to participate in the experimental phase of the study. For the experimental phase, each participant experienced three different music conditions (Preferred, Preset, and Silence) while performing a complex reading comprehension task.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…Likewise, the extraversion and introversion factor didn't have any significant difference in performance quality irrespective of the presence or absence of auditory simulations. This was again unlike previous findings (Furnham & Bradley, 1997;McDonald, 2013;Furnham &Strbac, 2002). Although, if the means of the performance between introverts and extraverts in the presence of auditory simulation is compared, extraverts did slightly better than introverts.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Likewise, the extraversion and introversion factor didn't have any significant difference in performance quality irrespective of the presence or absence of auditory simulations. This was again unlike previous findings (Furnham & Bradley, 1997;McDonald, 2013;Furnham &Strbac, 2002). Although, if the means of the performance between introverts and extraverts in the presence of auditory simulation is compared, extraverts did slightly better than introverts.…”
Section: Discussioncontrasting
confidence: 95%
“…The reliability variable is ranging from .85 to .90 for extraversion (Weaver & Kiewitz, 2006), for this study we would only be using the extraversion aspect of this personality questionnaire. This tool will help determine the factor of extraversion and introversion which seems to be a contributing factor in many studies dealing with this topic (Furnham & Strbac, 2002;McDonald, 2013;Gold et al, 2013;Nadler, 2010). For the prose retention task, 5 short prose passages taken from TOEFL sample questions (http://www.ets.org/toefl) consisting of different topics were selected and administered to a random sample of people who rated them on a scale of 1 to 5 (1 being very easy, 5 being extremely hard).…”
Section: Toolsmentioning
confidence: 99%
“…Another pattern that can be found in the literature concerns the moderating role of musical preference -the extent to which listeners enjoy the music style that is used as background or prime -in boosting the positive effects of music. Preference does not seem to change the Irrelevant Sound Effect (Perham and Vizard, 2011), but -at least in younger adults -it boosts the positive effects of background music on reading comprehension (Mcdonald, 2013), as well as those of musical primes on image encoding (Carr and Rickard, 2016): in both cases, preferred music outperforms silence, while non-preferred music does not. One explanation for the advantage of preferred music is that it is rewarding (Blood and Zatorre, 2001;Ferreri and Verga, 2016), and reward may be one mechanism subtending the positive effects of music on cognition (Ferreri and Verga, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…Based on the idea that non-task-concurrent music (prime) could keep the benefits of background music (arousal, reward or mood improvement) while minimizing its distraction-related costs, we predicted that music would have strong advantage over silence and/or environmental sounds. Concerning preference, we predicted an advantage of preferred over non-preferred music, based on previous findings (Mcdonald, 2013;Carr and Rickard, 2016) as well as on the principle that preference could maximize the reward component of music.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, McDonald (2013) investigated the link between preferred music genre and extroversion on reading performance. The result of his study showed that music could facilitate reading performance if the music which was listened to was what they preferred.…”
Section: Introductionmentioning
confidence: 99%